Examining Sense of Belonging Among Undergraduate Students in Speech-Language Pathology: Student Experiences and Recommendations for Improvement. - Ocampo, Alaine (Perspectives of the ASHA Special Interest Groups, 2026)
Purpose: This study examined sense of belonging among undergraduate students in a communication sciences and disorders (CSD) program, investigating differences across demographic groups and underlying reasons for belonging experiences. Given persistent workforce diversity challenges in speech-language pathology and audiology, understanding belonging patterns is critical for supporting student retention and professional identity development. Method: A convergent mixed-methods design was employed with 25 undergraduate students enrolled in a speech-language pathology program at a Hispanic-Serving Institution in Southern California. Participants completed an eight-item Sense of Belonging Scale and open-ended questions about belonging experiences and improvement suggestions. Quantitative data were analyzed using descriptive statistics, whereas qualitative responses underwent thematic analysis guided by an intersectional framework. Results: Overall belonging was positive (M = 2.07 on a 4-point scale), with faculty-related dimensions representing the strongest responses (80%-84%). However, demographic differences emerged: Students who identified as White reported consistently stronger belonging compared to students of color, who showed greater variability in experiences. Students of color comprised 92.3% of respondents providing improvement suggestions, identifying systemic barriers including limited diversity representation and inadequate social connection opportunities. Conclusion: Although CSD programs demonstrate strengths in faculty mentorship, demographic differences in belonging experiences suggest need for targeted interventions addressing representation, social connection, and academic support to enhance retention and workforce diversity.